Association of circulating omentin level and metabolic-associated fatty liver disease: a systematic review and meta-analysis - Zhang, Qin; Chen, Shuaihang; Ke, Yani; Li, Qicong; Shen, Chenglu; Ruan, Yuting; Wu, Kaihan; Hu, Jie; Liu, Shan (Frontiers in Endocrinology, 2023)
Background Metabolic-associated fatty liver disease (MAFLD) is closely associated with omentin, a novel adipokine that plays a vital role in metabolic balance. The literature about the relationship between circulating omentin and MAFLD is conflicting. Therefore, this meta-analysis evaluated circulating omentin levels in patients with MAFLD compared with healthy controls to explore the role of omentin in MAFLD. Methods The literature search was performed up to April 8, 2022, using PubMed, Cochrane Library, EMBASE, CNKI, Wanfang, CBM, Clinical Trials Database and Grey Literature Database. This meta-analysis pooled the statistics in Stata and presented the overall results using the standardized mean difference (SMD) and 95% confidence interval (CI). Results Twelve studies with 1624 individuals (927 cases and 697 controls) were included, and all of them were case-control studies. In addition, ten of twelve included studies were conducted on Asian participants. Patients with MAFLD had significantly lower circulating omentin levels than healthy controls (SMD=-0.950 [-1.724, -0.177], P=0.016). Subgroup analysis and meta-regression demonstrated that fasting blood glucose (FBG) might be the source of heterogeneity and was inversely associated with omentin levels (coefficient=-0.538, P=0.009). No significant publication bias existed (P>0.05), and outcomes were robust in the sensitivity analysis. Conclusion Lower circulating omentin levels were associated with MAFLD, and FBG might be the source of heterogeneity. Since Asian studies accounted for a significant portion of the meta-analysis, the conclusion might be more applicable to the Asian population. By investigating the relationship between omentin and MAFLD, this meta-analysis laid the foundation for the development of diagnostic biomarkers and treatment targets. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022316369.